Ameliorative effects of press mud and gypsum on soil quality, growth and physiology of guava (Psidium guajava) cultivar Hisar Safeda under RSC water irrigation - AKSHAY; RAJKUMAR; SINGH, MANENDER; KUMAR, ASHWANI; SINGH, NIRMAL (The Indian Journal of Agricultural Sciences, 2026)
Presence of Residual sodium carbonate (RSC) in irrigation water is a critical threat to agricultural sustainability as it deteriorates soil structure and fertility due to high sodium concentration. This experiment was conducted during 2021 to 2023 at ICAR-Central Soil Salinity Research Institute, Karnal, Haryana to evaluate the effects of sodic water irrigation with or without amendments (press mud and gypsum) on soil quality, growth, physiological and biochemical parameters of guava (Psidium guajava L.) cultivar Hisar Safeda. Ten different treatments including best available water (non-sodic water as control) and 3 RSC levels (2.5, 5.0 and 7.5 meq/L) with or without amendments were arranged in RBD with five replications. The results demonstrated that increasing RSC levels raised soil pH but reduced nitrogen and phosphorus availability, significantly impacting growth and physiological parameters. Growth and physiological traits declined with higher RSC, with the lowest values at 7.5 meq/L without amendments. Conversely, proline content and antioxidant enzyme activities increased under elevated sodicity, reflecting stress responses. Amendments improved growth, physiological and biochemical traits at all RSC levels, with gypsum outperforming press mud, likely by supplying essential nutrients and improving soil ionic balance. Results indicated that Hisar Safeda could be irrigated with sodic water up to RSC 2.5 meq/L with amendments without any noticeable reduction in growth and physiological parameters, suggesting it as a viable sustainable practice for guava cultivation under sodic conditions. The present study also offers valuable insights for sustainable management of sodic water and soils using amendments like gypsum and press mud to maintain productivity and soil health.